The Historiography of China's "Rise": A Struggle for Narrative Autonomy in IR Theory. - Wilde, Jarrett T.; Xing, Yue (Asian Studies Review, 2020)
The story of International Relations (IR) has always been recounted with a language endemic to the Anglo-liberal political and international experience. This vernacular depicts all states as self-interested expansionists seeking to either promote or antagonise the liberal international order. To advance the meta-theoretical debate on cultural pluralism in IR, this article explores the projection of liberal ontological paradigms onto the historiography of China's "rise". The narrative frames from "theories of foreign policy" depict China as a rational calculator seeking material maximisation. The narrative frames from "theories of international politics" depict China as a revisionist state to be evaluated, managed and contained according to the standards set by Anglo-liberal orthodoxy. This article explores China's "rise" as a struggle for narrative autonomy: a mission to identify and express itself in its own terms. In IR theory, this struggle manifests itself in the concepts of wangquan, zhongyong and tianxia that articulate China's political and international experience using an indigenous vernacular. By situating these different perspectives in a context of cultural relativity, we provide a conceptual detour around the conventional binary discourse that regulates the present debate: one that seeks to acknowledge ontological difference without descending into historiographical antagonism.